Praktik ESG terhadap Profitabilitas Perusahaan dengan Kepemimpinan berkelanjutan sebagai Variabel Moderasi - Ksatrya Swarga Putera Farihadhy; Idrianita Anis (Journal of Management and Bussines (JOMB), 2024)
This research aims to examine the impact of ESG (environmental, social and governance) practices on company profitability and the moderating role of sustainable leadership in this influence. Data was obtained from 51 different companies with a total of 357 samples using purposive sampling techniques. Analysis was carried out using Eviews 12 and multiple linear regression methods and moderated regression analysis (MRA). The results of the analysis show that ESG practices as a whole have a significant positive impact on company profitability. However, when broken down, sustainability intentions have an insignificant negative impact, while sustainability integration and implementation have an insignificant positive impact on profitability. Additionally, sustainable leadership moderates the impact of ESG practices on profitability, turning the impact into an insignificant negative. In conclusion, the importance of ESG practices and the important role of leadership in strengthening their impact on company profitability. Keywords: Sustainable Leadership, Profitability, ESG Practices